Pemetaan Sebaran Lokasi Gedung Apartemen Di Surabaya Menggunakan Sistem Informasi Geografis (SIG) - Citra, Rangga Surasa (Universitas Negeri Surabaya, 2023)
This article aims to analyze the pattern of distribution of apartment buildings in the city of Surabaya using the Nearest Nighbor Analysis method. The research was conducted using ArcGIS 10.8 software and data on the coordinates of apartment buildings in four Surabaya areas, namely South Surabaya, West Surabaya, Central Surabaya and East Surabaya. The results showed that the distribution pattern of apartment buildings in the South Surabaya area is included in the category of uneven distribution (random), while the West Surabaya area has a cluster pattern of distribution. In Central Surabaya and East Surabaya, the distribution pattern of apartment buildings is categorized as a dispersed pattern. The range of the spread of apartment buildings is also analyzed by considering the accessibility and effective distance for pedestrians. This study provides an overview of the pattern of distribution of apartment buildings in the city of Surabaya and can be used as a reference in planning the development of apartment areas.